Microstructural evolution in laser-based directed energy deposition of 316 L stainless steel with interlayer deformation - Mithal, Abeer (2024)
There has been a significant industrial interest in additive manufacturing (AM) technologies such as directed energy deposition (DED) due to their ability to produce complex geometries with controlled microstructures. More recently, AM processes have been hybridized with plastic deformation technologies to achieve further benefits. In this experimental work, we systematically investigate the microstructural evolution in a DED process, selectively coupled with interlayer deformation using 316 L stainless steel. Our results revealed that the region below the interlayer deformed surface comprised of a recrystallized zone and a retained deformation zone with increased hardness in both zones. The region above the interlayer deformed surface experienced a refined solidification at both the grain and the sub-grain levels, which was attributed to the change in nucleation conditions due to the interlayer deformation. Moreover, microstructural evolution was found to vary significantly under different deformation levels and DED parameters. The extent of the recrystallized zone increased with increasing interlayer deformation level and decreased with faster scan speed. The findings provide comprehensive insights into the microstructural evolution in AM processes coupled with interlayer deformation and could pave the way for quick and cost-effective methods to engineer microstructures for different applications.